Highly sensitive and selective colorimetric and plasmonic sensor of Fe2+ based on gold nanostructures biosynthesized with Opuntia joconostle fruit peel - Eric Reza-Sámano; Rosa Gómez-Sánchez; Alan Peñaloza-Garduño; Raúl A. Morales-Luckie; Oscar F. Olea-Mejía; María Guadalupe González-Pedroza; Victor Sánchez-Mendieta (Discover Nano)
Abstract Biogenic gold nanostructures have been obtained, for the first time, by bio-reduction of Au3+ ions with an aqueous extract of Opuntia joconostle fruit peel (Oj-AuNPs). This particular methodology is completely green, since room temperature was used, and no infusion preparation was required. The Oj-AuNPs exhibit a broad surface plasmon resonance (SPR) signal, with a maximum at 556 nm. SEM and TEM observations show Oj-AuNPs with mean size around 80 nm and raspberry-like morphologies, mainly, made of smaller nanoparticles glued by the biomass. When freshly prepared Oj-AuNPs solution is placed in contact with Fe2+, the solution changes from brown to a green-grayish color, being the only metal ion changing the Oj-AuNPs solution color among the other twelve metal ions probed, including Fe3+. Once the Fe2+ ions are detected, the SPR of the Oj-AuNPs becomes broader with a considerable red shift. Furthermore, smaller Au nanostructures, with better defined morphologies than those in the original Oj-AuNPs, are observed by TEM. Therefore, the conceivable mechanism of the naked eye and plasmonic detection of Fe2+ by Oj-AuNPs involves the disaggregation of the original larger gold nanostructures. Sensitivity studies of the Oj-AuNPs detection of Fe2+ were performed from 200 ppm to 0.1 ppb. The limit of detection (LOD) and limit of quantification (LOQ) for Fe2+ are 0.023 and 0.079 ppb, respectively. Moreover, the Oj-AuNPs colorimetric sensor was effectively tested for highly sensitive detection of Fe2+ in tap water.